Small Hydropower—Small Ecological Footprint? A Multi-Annual Environmental Impact Analysis Using Aquatic Macroinvertebrates as Bioindicators. Part 1: Effects on Community Structure - Scotti, Alberto; Jacobsen, Dean; Ștefan, Valentin; Tappeiner, Ulrike; Bottarin, Roberta (Frontiers in Environmental Science, 2022)
The increasing incentives stemming from many international initiatives that target sustainable energy production have led to the global success of small hydropower plants. However, there is a growing debate about the actual environmental impact these structures have on riverine ecosystems, to the extent that some researchers argue that they could have a proportionally greater impact than large hydropower plants; however, an empirical evaluation applying a long-term true “Before-After-Control-Impact (BACI)” approach has never been conducted. In a true “BACI” experiment applying generalized linear mixed models, we assessed changes in benthic macroinvertebrate communities – taxonomic composition, spatial and temporal β-diversity, and possible indicator taxa – along 6 sites located in a glacier-fed stream in the Italian Alps before and after the installation of a small “run-of-river” hydropower plant. The “BACI” results over the 5-year study showed no significant variation in the benthic macroinvertebrate communities stemming from the activity of the hydropower plant. Moreover, spatial β-diversity showed, in relation to the “control” site, a constant dissimilarity pattern throughout all the sampling years, exhibiting a constant increase proceeding downstream. On the other hand, temporal β-diversity showed changes in the benthic macroinvertebrate communities, but these changes were largely caused by variation in densities and not by the appearance or disappearance of new taxa. In summary, we were unable to detect a significant impact of the small “run-of-river” hydropower plant on the benthic macroinvertebrate communities of the glacier-fed stream under study. Despite the need of further studies that consider the different features and operational measures of small hydropower plants, our findings illustrate that, when correctly managed, small hydropower plants and the energy they produce may represent an added resource for strategic debates on energy planning processes, especially in light of the commitments at the international level of many countries in developing strategies toward a “carbon-neutral” energy sector.